Managing Differences as Internationalization Strategy; A Case of Daiso Japan Entry to Indonesia - Inke Maria; Vinsensio MA Dugis (Global Strategis, 2017)
It has been widely accepted that multinational corporations (MNCs) have been part of important agencies playing critical role in determining global governance. Increasing globalization, featuring in various forms, have critically facilitated the operation of MNCsglobally and increasing influence of MNCs on global politics. However, differences that could come in the forms of culture, politics, geography, and economy, are still crucial obstacles forMNCs competing internationally. Therefore, building and employing a spot-on international strategy becomes a crucial issue. Taking-up a Daiso Japan entry to Indonesia as a case study, this article higlights how cultural adaptation could become a key success for an MNC. Equally, it reveals how far culture is needed by Daiso Japan when doing its international expansion into Indonesia. The case informed that some cultural elements such as language, customs,and manners can be instrumental elements supporting the success of employing cultural adaptation as an international strategy. These cultural elements are potential sources for adjusting with local culture through aggregation process.